PENGARUH KINERJA LINGKUNGAN DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN RISK MINIMIZATION SEBAGAI VARIABEL MODERASI - Muhamad Amarrulloh; Dea Annisa (Pusat P2M Politeknik Negeri Batam, 2023)
This study aims to examine and obtain empirical evidence regarding the Effect of Environmental Performance and Audit Committee on Corporate Social Responsibility Disclosure with Risk Minimization as a Moderating Variable. The population in this study are non-financial sector companies listed on the Indonesia Stock Exchange in 2017 – 2021. The data collection technique in this study uses secondary data with the data collection method, namely documentation. The sample collection technique for this research was purposive sampling using the Eviews 9 media software. This study used samples obtained from 13 non-financial sector companies, the analysis technique used was panel data regression. The research used is an associative quantitative approach. The results of this study indicate that Environmental Performance has no effect on Corporate Social Responsibility Disclosure, Audit Committee has no effect on Corporate Social Responsibility Disclosure, Risk Minimization cannot moderate the effect of Environmental Performance on Corporate Social Responsibility Disclosure, and Risk Minimization cannot moderate the effect of Audit Committee on Corporate Social Responsibility Disclosure.